A Method to Evaluated Gas Content with Coalbed Methane Reservoir Based on Adsorption Theory and Production Analysis. (3rd June 2022) - Feng, Ruyong
Abstract : In the process of coalbed methane development, the gas content not only determines the reserves of methane in coal reservoir but also is the most important geological parameter affecting the production of coalbed methane. The gas content directly determines whether coalbed methane can be developed efficiently. However, in the current development evaluation process, it is very difficult to accurately predict the gas content in coal seams. An efficient and accurate method to predict gas content has not been found yet. This is mainly restricted by the development mode and technology of coalbed methane. In the current low-cost development model, gas content test data are relatively scarce. Under such circumstances, it is difficult to accurately evaluate the distribution of CBM gas content in the whole area. At the same time, the gas content of coalbed is the key parameter for efficient development of coalbed methane. Under normal circumstances, gas content heterogeneity will result in a large gap between development effects in different regions. At present, there is no evaluation method for gas content parameters of coal reservoir. Under this background, the key parameters of coalbed methane development in southern Qinshui Basin were evaluated. On the basis of systematically summarizing and understanding the development law of coalbed methane in different types of coal reservoirs, a gas content evaluation method based on adsorption theory and production dynamic analysis is proposed. Combined with the coalbed methane production model and isothermal adsorption model, the critical desorption pressure can be calculated accurately by using the bottom hole pressure when casing pressure occurs in production wells. The critical desorption pressure correction model of coalbed methane was innovatively established. Langmuir equation was used to accurately characterize the adsorption characteristics of coalbed methane. Forming a new method for gas content prediction in the case of fewer coring wells. The gas content evaluation technology coupled with isothermal adsorption theory and production dynamic analysis saves the development cost of coalbed methane and improves the prediction accuracy of coal seam gas content in noncoring wells. At the same time, there is a good relationship between the predicted results and the measured gas content at well points. The coincidence rate reached 97.37%. This technology can effectively improve the prediction accuracy of coal seam gas content. This technique is suitable for the productivity evaluation of coalbed methane reservoir. It can also provide scientific basis for the development and reserve evaluation of coalbed methane reservoirs at home and abroad.